Indonesia or China: Which Country Has The Rightful Claim Over North Natuna Sea - Azahra Haisy Tasya,; Nuzul Shinta Nur Rahmasari,; Muhammad Alfarizhi,; Tomy Michael, (Technium Social Sciences Journal, 2021)
This research was aimed to give explanation about the conflict between Indonesia and China over North Natuna Sea according to UNCLOS 1982 and Permanent Court of Arbitration, also give explanation about the solution that both countries may take. This research used qualitative and descriptive method which is discusses the phenomena as well as the way to solve the problem. China’s claiming North Natuna Sea is a part of Nine-dash line it created. This action made Indonesia became furious. The result of this research concludes that China’s claim over North Natuna Sea is against the Unclos 1982 and Permanent Court of Arbitration’s statetement that makes the claim ilegal.